On the Behavior of a System of Rational Difference Equations xn+1=xn-1/(ynxn-1-1),yn+1 = yn-1/(xnyn-1-1),zn+1=1/xnzn-1 - Liu Keying; Wei Zhiqiang; Li Peng; Zhong Weizhou (Discrete Dynamics in Nature and Society)
We are concerned with a three-dimensional system of rational difference equations with nonzero initial values. We present solutions of the system in an explicit way and obtain the asymptotical behavior of solutions.